ACADEMIC WRITING DIFFICULTIES FOR INDONESIAN STUDENTS IN PURSUING POSTGRADUATE STUDIES ABROAD - Rosidah Wulan Ningrum; Hamamah Hamamah; Sahiruddin Sahiruddin; Zuliati Rohmah (Premise: Journal of English Education and Applied Linguistics, 2023)
Academic writing skills have become an essential aspect that Indonesian students must focus on,  especially for those who are planning or pursuing their postgraduate studies abroad. The current research is conducted to investigate the difficulties faced by Indonesian students who currently pursue or recently complete their postgraduate studies in seven countries with different majors. The subject was seven Indonesian students who studied in India, Australia, the United Kingdom, Ireland, Netherland, and Poland. To collect the data, the researcher used the qualitative research method. Two questionnaires in the form of open-ended questions were distributed and fulfilled by all research participants. The findings indicate that Indonesian students who pursued postgraduate study abroad faced difficulties in academic writing practice, for instance, paraphrasing the sentence, assuring coherence, formulating cohesion, and expressing their voice. Besides, some of them also faced problems in choosing appropriate words and relevant topics in their writing. The main factors that appear to particularly contribute to the difficulties are less academic writing practice, lack of vocabulary, and unfamiliar with academic writing structure. Even though the students pursued different majors and countries, they have common difficulties in order to write academic writing. Moreover, cultural differences also influence students’ difficulties.